Kerjasama UMKM Kota Sumedang Dengan Kota Fukuoka Jepang Dalam Meningkatkan Ekspor Gula Aren Semut Tahun 2020-2023 - Mirantika, Alvina Virda; Finaldin, Tom (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Cooperation between UMKM in Sumedang City and Fukuoka City, Japan, is carried out in the economic sector. The cooperation is included in efforts to develop the local economy by utilizing the potential of regional superior products to the fullest. Ant palm sugar, which has high nutritional value and has a very potential market in Japan, is the main focus of this cooperation. With this collaboration, Sumedang UMKM not only get access to the international market, but also increase production capacity and product quality according to international standards. In addition, this cooperation also strengthens the relationship between Sumedang City and Fukuoka City. The purpose of this research is to answer the problems that have been determined, namely to explain how the cooperation between Sumedang and Fukuoka in the export of ant palm sugar, identify obstacles that occur during cooperation, and find efforts to overcome these obstacles. This research method uses a qualitative approach. This research uses the theory of international cooperation, international trade, and liberalism. The data collection techniques used include interviews, documentation, and observations. In data analysis, data reduction, data presentation, and conclusion drawing methods are used. The results of the research are expected to be an example or model in sustainable economic development through synergy between the local sector and the global market. This analysis will also review how local economic diplomacy strategies can encourage the growth of MSMEs and increase export opportunities, as well as their impact on the welfare of the people in both cities.